Contactless Resonant Cavity Dielectric Spectroscopic Studies of Cellulosic Paper Aging. (11th February 2020) - Kombolias, Mary; Obrzut, Jan; Postek, Michael T.; Poster, Dianne L.; Obeng, Yaw S.
Abstract: The current analytical techniques for characterizing printing and graphic arts substrates, particularly those used to date and authenticate provenance, are destructive. This limits the amount of data that can be captured from an individual sample. For samples being evaluated in forensic and archeological investigations, any loss or degradation of the materials is undesirable. Furthermore, it is difficult to produce statistically relevant data for such analytes. We have shown elsewhere that a contactless microwave resonant cavity dielectric spectroscopy technique can discriminate between paper samples made from different plant fiber species based on their lignin content. In this publication, we demonstrate the utility of the contactless resonant cavity dielectric spectroscopy (RCDS) technique in the characterization of naturally and artificially aged paper samples. Based on our experimental results, we suggest that the technique could be used in forensic and archeological investigations of unique paper products.